2010
DOI: 10.5399/osu/jtrf.45.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Pricing, and Profitability in the U.S. Rail Freight Industry, 1995-2004

Abstract: Rail industry productivity grew by 7% per year from 1984 to 1995, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Deregulation ushered in a dramatic decline in railroad rates-rates on average were cut in halfand a dramatic rise in railroad profi ts (Figure 1.1). The explanation was a dramatic rise in productivity due to industry consolidation, the abandonment of uneconomic lines, the growth of long-haul coal and intermodal traffi c, and a far more intensive use of a "right-sized" railroad system (Caves, Christensen, andSwanson 2010-2011;Martland 2012;Stover 1997).…”
Section: Background For Reform: the 1980s Watershedmentioning
confidence: 99%
See 1 more Smart Citation
“…Deregulation ushered in a dramatic decline in railroad rates-rates on average were cut in halfand a dramatic rise in railroad profi ts (Figure 1.1). The explanation was a dramatic rise in productivity due to industry consolidation, the abandonment of uneconomic lines, the growth of long-haul coal and intermodal traffi c, and a far more intensive use of a "right-sized" railroad system (Caves, Christensen, andSwanson 2010-2011;Martland 2012;Stover 1997).…”
Section: Background For Reform: the 1980s Watershedmentioning
confidence: 99%
“…5 Workforce reductions had been major contributors to carrier profi tability since the end of the Second World War. Key drivers of carrier profi tability continued to economize on labor, such as the use of larger cars and longer trains and the shift to intermodal freight traffi c (Martland 2012). Railroad employment fell by 9,000 workers from 2001 to 2002, when 60/30 was introduced-more than the increase in retirements attributable to the 2001 reform-and by another 4,000 in 2003.…”
Section: The Carriers and The 2001 Reformmentioning
confidence: 99%
“…Access to the network and dispatching flexibility is more constrained in Europe. Additionally, in the U.S., investments in the past 40 years were focused on increasing freight trains' productivity (Martland 2012) by: increase in train length (with associated changes in terminals and increase in sidings); increase in the net weight per rail car; and increase in track resistance and double stacking of containers (with the associated increase in clearances). In Europe, investment was concentrated on passenger services, namely, high speed rail.…”
Section: Modal Share and Structural Differencesmentioning
confidence: 99%
“…Carl D. Martland (2006) studies the extent and sources of productivity enhancement in the U.S. rail industry since 1995, and whether productivity improvement has led to improved financial performance. His study concludes that from 1995 to 2004, rail productivity increased 5% per year, there was a decline in rail prices, and financial performance was also not showing much progress.…”
Section: Review Of Literaturementioning
confidence: 99%
“…His study concludes that from 1995 to 2004, rail productivity increased 5% per year, there was a decline in rail prices, and financial performance was also not showing much progress. Martland (2006) revealed that by 2004, the long-term productivity trends in the rail industry were almost coming to an end coupled with the decline in the rate of productivity and increase in rail rates.…”
Section: Review Of Literaturementioning
confidence: 99%